2008
DOI: 10.1039/b805777j
|View full text |Cite
|
Sign up to set email alerts
|

Cationic cyclocholamides; toroidal facial amphiphiles with potential for anion transport

Abstract: Cholic acid has been transformed into cyclotrimeric and cyclotetrameric toroidal amphiphiles with inward-directed ammonium substituents; the cyclotrimer effects the transport of chloride anions across vesicle bilayer membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 28 publications
0
43
0
1
Order By: Relevance
“…A subsequent assay in which a second anion (bicarbonate) was added to the external sulfate medium showed that chloride transport by compounds 1-4 was restored, clear evidence that these compounds facilitate HCO 3 -/Cl -exchange across phospholipid membranes. 13 C NMR assays provided direct evidence for transmembrane bicarbonate transport, as the intraand extra-vesicular carbon-13 labelled bicarbonate populations could be clearly distinguished. This NMR data, when combined with results from the Cl --selective electrode experiments, firmly establish that compounds 1-4 enable the transmembrane exchange of Cl -/HCO 3 -anions.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…A subsequent assay in which a second anion (bicarbonate) was added to the external sulfate medium showed that chloride transport by compounds 1-4 was restored, clear evidence that these compounds facilitate HCO 3 -/Cl -exchange across phospholipid membranes. 13 C NMR assays provided direct evidence for transmembrane bicarbonate transport, as the intraand extra-vesicular carbon-13 labelled bicarbonate populations could be clearly distinguished. This NMR data, when combined with results from the Cl --selective electrode experiments, firmly establish that compounds 1-4 enable the transmembrane exchange of Cl -/HCO 3 -anions.…”
Section: Discussionmentioning
confidence: 96%
“…After addition of transporters (isophthalamide 3 in Figure 3a and prodigiosin 4 in Figure 3b), a sharp 13 C NMR signal for H 13 CO 3 -( ~161 ppm) was restored. This renewed 13 C NMR signal must be caused by ligand-mediated transport of HCO 3 -into the liposome since the paramagnetic Mn 2+ is impermeable to the phospholipid bilayer. Importantly, the control experiment in which DMSO was added without transporter, did not result in any restoration of 13 C NMR signal (Figure 3c).…”
Section: Figure 1 (A)mentioning
confidence: 99%
See 3 more Smart Citations